PORTRAIT OF LEARNING ENGLISH AT MI DARRUN NAJJAH - Ferri Hidayad; Ariya Agustin; Marsinah Marsinah; Muhammad Bambang Purwanto (Universitas Wiralodra, 2023)
The problem faced by English students when learning English at MI Darrun Najjah Prabumulih, Sumatra Selatan was how to make all students focus on the learning material and be active, considering that not all students can focus on what is conveyed and often there were students who also busy playing cellphones. To overcome this problem, the English teacher sometimes asked students some questions to regain their learning intention. The objective of this research were to find out the strategies in teaching listening to students of MI Darrun Najjah Prabumulih and the problems found by the English teacher in teaching listening as well as how they overcome the problems. The research was conducted by using descriptive qualiitative research. This research was carried out at MI Darrun Najjah Prabumulih. The subject of this research was a English teacher. The research collected the data through interview guidance and used library research, which compiles extensive documentation on a single or a number of topics. Both original sources and secondary sources are used in this investigation. In conclusion, according to the context, conditions, and daily situation of the students. It is recommended that the result of the study needs to be integrated into the communication media which is appropriate to the needs of the students.